Serendipitous synthesis of 3-hydroxy tetrahydrofurans from tin catalyzed sulfonylation of acyclic 1,2,4-triols - Makhosazana, P.; Gamedze, Rejoice; Maseko, B; Chigondo, Fidelis; Nkambule, Comfort, M. (Elsevier, 2016)
The reaction of syn-1,2,4-triols under sulfonylation conditions catalyzed by Bu2SnO (5 mol %) results in cyclization and the formation of 3-hydroxy tetrahydrofurans (56–85%) while the anti-1,2,4-triols react to give C1-O-sulfonyl derivatives in good yields (66–83%) and the cyclization product in poor yield (5– 12%). A mechanism that justifies these observations is proposed to occur via the tosylation of the primary hydroxyl followed by an intramolecular tin acetal rearrangement to a 1,3-stannylene which then undergoes a 5-exo-tet-cyclization. The difference in rates of cyclization reactivity is due to the energetically more stable tin acetals of syn-1,3-diols compared to those of anti-1,3-diols.